Postawa ziemian galicyjskich wobec przemysłu – wystawa przemysłowo-rolnicza w Jaworowie w 1907 r. - Komorowski, Jerzy (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
This article contains information about little known event which was the exposition of agrarian and industrial achievements of Javoriv region near Lvov in 1907. Author presented and partially described the event. It was also possible to expose the social and political context of this event. The conclusion seems to be that promoting industry and modern methods in farming was only a partial goal of landowners from Javoriv region. Political reasons, especially the forthcoming election to parliament in Lvov was also very important. Using the classical theoretical concept of attitude, author tries to analyze the social and political background of attitude to industry of landowners in the region. The conclusion is that industry in the Javoriv region played a subsidiary role for land estate, which was the basis of economical and political domination of landowners in the region at the time.